Pergeseran Budaya dan Tradisi Lokal Dalam Kehidupan Masyarakat Sumatera Utara - II, Harianto; Amin, Teguh Satria; Zulfitri, Zulfitri (Indonesian Research Journal on Education, 2021)
The diversity of ethnic groups in Indonesia gives rise to many cultures, traditions and local wisdom that live and develop in society. Culture itself is divided into several sectors that support various kinds of community life. Local wisdom in North Sumatra has many types and also diversity. And this research was conducted to see the shift in cultural values and local traditions in the lives of people in North Sumatra. This study uses data analysis with a qualitative descriptive method. This method is an analysis that tries to provide a picture based on the facts obtained in the field. These data are of course supported by primary and secondary data to support this research process. This qualitative research is presented with a description and also assisted with the calculation of numbers, percentages obtained in the process of collecting and analyzing data. These data were analyzed by means of descriptive. Concept development, data collection and facts regarding shifts in cultural values and local traditions in the lives of the people of North Sumatra, underwent a process in this globalization era. And this research shows that there is a shift in values in culture and traditions as well as local wisdom in North Sumatra which certainly has an impact on shifts in the community environment.